Identifying factors contributing to the delay of project timelines in public- private partnerships for housing development projects in Namibia - Mberema, Maria-Magdalena (Department of Construction Economics and Management, 2023)
Public-Private Partnerships (PPPs) have recently gained widespread acceptance as a method of housing provision in several nations. The joint venture strategy is used in the majority of PPP housing development projects, which allows the local government to retain control over planning and development while utilizing the private partner's existing resources and experience. Timeliness delays in PPP projects are a typical occurrence in Namibia and around the world. The goal of this study was to identify the key factors that create delays in the timeframes of PPP housing development projects in Namibia. The study adopts the inductive approach since the aspects of housing and Namibian context is relatively new with limited existing literature. The case study research was applied to this research using a mixed-method of quantitative and qualitative research design. Using a purposive sampling method, two officials from the local authority (CoW), two officials from the built environment professionals, and two PPP experts were selected for the interviews and ten property developers who have been involved in PPP housing development were selected and forwarded the online questionnaire where only four responded in this study. The researcher used descriptive analysis to analyse the quantitative data. By adopting semi-structured interviews, the researcher had a list of different questions for the different sectors. The researcher used thematic analysis to analyse the qualitative data. The researcher identified 15 key factors that cause a delay in timelines of PPP housing development projects in Namibia which are namely: (1) Allocation; (2) Availability of land; (3) Funding; (4) Internal Factors from CoW/Delays from the Local Authorities; (5) Lack of Project Management; (6) No capacity; (7) Political Will/Bureaucracy; (8) Procurement; (9) Tenure ship; (10) Town Planning/Delays in Statutory Planning Approvals; (11) Understanding of PPP implementation/Lack of understanding in PPP processes; (12) Inadequate working relationships; (13) Corruption; (14) Lack of clear PPP Policies to be managed; and, (15) No streamlined processes. According to the findings, (2) Availability of land, (4), Internal Factors from CoW/Delays from the Local Authorities and (10) Town Planning/Delays in Statutory Planning Approvals stood out as factors experienced in Namibia only. The researcher offers the following recommendations to be explored; Central Government support, Establishment and Implementation of Project and Programme Management Office in the local authority (City of Windhoek), Project-Based Consultation and Training Workshops and finally a comprehensive investigation on PPP housing development projects delivered on time. Lastly, the study concluded six measures to mitigate delays in timelines of PPP housing development projects in Namibia. From the six mitigation measures the main ones that stood out is for the City of Windhoek to have strategies in place for forward planning of PPP projects and learn from pervious projects and for the Local Authority to reduce their involvement in projects which often lead to bureaucracy in statutory approvals.